2022
DOI: 10.1037/adb0000808
|View full text |Cite
|
Sign up to set email alerts
|

Decision strategies while intoxicated relate to alcohol-impaired driving attitudes and intentions.

Abstract: Objective: Approximately 28 million individuals engage in alcohol-impaired driving (AID) every year. This study investigated individuals' AID decision making strategies under intoxication, their variability across the breath alcohol concentration curve (BrAC), and the association between strategy and AID attitudes and intentions. Method: 79 adults (23.9 years, 57% women) who drank alcohol ≥2 days per week and lived >2 miles away from their typical drinking locations completed an alcohol administration protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Many task respondents report heavy reliance on paid rideshare services for commuting, more so after a night of consuming alcohol, and even when those services are relatively more expensive. Recent work shows that the cost of alternative transportation (e.g., rideshare) may play a significant role in predicting alcohol‐impaired driving among some recipients (McMullin et al, 2022). The low rate of response allocation toward the alcohol‐impaired driver option and the higher rate of allocation toward the walk‐alone condition is notable.…”
Section: Discussionmentioning
confidence: 99%
“…Many task respondents report heavy reliance on paid rideshare services for commuting, more so after a night of consuming alcohol, and even when those services are relatively more expensive. Recent work shows that the cost of alternative transportation (e.g., rideshare) may play a significant role in predicting alcohol‐impaired driving among some recipients (McMullin et al, 2022). The low rate of response allocation toward the alcohol‐impaired driver option and the higher rate of allocation toward the walk‐alone condition is notable.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that risk attitude is a domain-specific effect (Blais & Weber, 2006;Hanoch et al, 2006) and that the rate at which individuals satisfy transitivity may differ across different types of choices (e.g., Hatz et al, 2020). In a prior study using a similar binary-choice paradigm, we tested alcohol's effects on decision-making strategies for alcohol-impaired driving decisions and found that some individuals switched strategies between the ascending and descending limbs of the BrAC curve (McMullin et al, 2022). These classifications do not map directly onto those tested in the current study, yet this pattern of results suggests that choice preference structure may be more susceptible to alcohol's effects in some domains than in others.…”
Section: Discussionmentioning
confidence: 99%
“…An important direction for future research is to leverage modeling techniques to other behavioral domains. Models of decision-making have been used to better understand how individuals choose to engage in alcohol-impaired driving (McCarthy et al, 2021;McMullin et al, 2022), and could also be applied to other types of risks associated with drinking (e.g., aggression, binge drinking, other substance use). Quantifying how alcohol impacts decision-making across various domains of behavior could promote development of stronger theories of alcohol's impacts on behavior.…”
Section: Integrative Discussionmentioning
confidence: 99%